The Impact of Logo Design Towards Customer’s Brand Image Perception: A Research of Logo Shapes And Colors in The Hotel Industry - Munawaroh Munawaroh (Journal of Business on Hospitality and Tourism, 2015)
Brand image is how a brand perceived by the customer. The brand image perception shaped by certain attributes of the company that has been delivered through Corporate Visual Identity (CVI). CVI is a visible elements of a brand, often regarded as one aspect that creates company’s image through logo or symbol. The purpose of this research was to determine the significant impact between shapes and colors used in logo design and customers’ brand perception in hotel industry. This research was done with quantitative method where the data was primarily collected through distributing the questionnaires. The data collecting process involves 100 respondents who reside in the Greater Jakarta Area. Multiple regression analysis in SPSS version 21.0 was used to analyze the data. The result of this research showed that both shapes and colors used in the logo have strong impact on how brand image perceived by the customers. Shapes of the logo influence the brand image perception with a percentage of 92.5%, while colors affect the brand image perception with a percentage of 92.4%. Based on the result, it can be concluded that applying certain shapes and colors in the logo design can help hotel industry to enhance the desired brand image and create a strong brand positioning in the market.